We begin at the end - Whitaker, Chris (Henry Holt and Company, 2021)
"Thirty years ago, a teenage Vincent King was sent to prison. But now, he's served his sentence and is returning to his hometown. The hometown where his childhood best friend, Walk, is now the chief of police. The town where his childhood sweetheart, Star Radley, still lives. The same Star Radley whose sister he killed. Duchess, Star's daughter, is a self-proclaimed outlaw. She needs to be. Who else is going to take care of her and her five-year-old brother? Star is still dazzling, still beautiful, but she hasn't shined as bright since Vincent was sent away. Too often it's Duchess and Walk who are the ones taking care of her. But when Duchess exacts her own vigilante revenge, she will set into motion a series of events that threatens not only her own family, but everyone she grows close to. A crime thriller that will break your heart and a literary novel with a mystery at its core, We Begin at the End unforgettably examines how the choices we make can nudge us into the dangerous ground between good and evil"--